TINJAUAN HUKUM TERHADAP PENERAPAN BIOTA LAUT YANG DILINDUNGI (STUDI KASUS NOMOR 34/Pid.B/2020/PN.Mks): LEGAL REVIEW ON THE IMPLEMENTATION OF PROTECTED MARINE BIOTA (CASE STUDY NUMBER 34/Pid.B/2020/PN.Mks) - Basri, Nurwana; Hasan, Yulia A.; Zubaidah, Siti (Clavia, 2022)
This study aims to determine. How is the application of material law in the decision Number: 34/Pid.B/2020/PN.Mks. And whether the sanctions given to the perpetrators in the decision Number: 34/Pid.B/2020/PN.Mks have been in accordance with the values of justice. This study uses a qualitative research type, the types of data used are primary data and secondary data, data from primary materials was obtained directly through information using interview techniques with the Makassar District Court and the Center for Conservation of Natural Resources and data from secondary materials refer to laws, books, journals, and information obtained from the results of questionnaires/questionnaires with fishermen and the community at Lelong Market Makassar. The results of this study indicate that the application of material law in the decision number: 34/Pid.B/2020/PN.Mks is in accordance with Law Number 5 of 1990 concerning Conservation of Biological Natural Resources and Their Ecosystems Article 40 Paragraph (2) jo Article 21 paragraph (2) letter d. the sanction given to the perpetrator in the decision Number: 34/Pid.B/2020/PN.Mks according to the judge was appropriate but according to the author it was not in accordance with the consequences of the defendant.